Revolution in Zanzibar an American's Cold War tale - Petterson, Donald (Oxford Westview, 2002)
The Cold War exploded in Zanzibar in 1964 when African rebels slaughtered one of every ten Arabs. Led by a strange, messianic Ugandan, Cuban-trained factions headed the rebels, making Zanzibar (in the eyes of Washington) a potentially cancerous base for the communist subversion of mainland Africa. Exotic Zanzibar ? fabled island of spices, former slave-trading entrept̥, and stepping-off point for 19th century expeditions into the vast interior of the Dark Continent ? had succumbed to the terror of 20th century revolution and Cold War intrigue.In the vivid, eyewitness tradition of The Bang Bang Club and The Skull beneath the Skin, Donald Petterson weaves an engrossing tale of human drama played out against a background of violence and horror. As the only American in Zanzibar throughout the revolution, Petterson reports with the inside authority of a highly placed diplomatic observer, illuminating how the current troubles in Zanzibar are rooted in the Cold War and the revolution of 1964.
Includes bibliographical references (p. 273-276) and index.
Keywords: Zanzibar-History-Revolution